Endometrial Thickness Is a Risk Factor for Singleton Low Birth Weight From Single Blastocyst Transfer: A Retrospective Cohort Study - Du, Mingze; Zhang, Junwei; Liu, Manman; Guan, Yichun; Wang, Xingling (Frontiers in Endocrinology, 2021)
Objective: To explore whether endometrial thickness (EMT) ≤7.5 mm is associated with singleton low birth weight (LBW) from single fresh blastocyst transfer. Methods: This was a retrospective cohort study. Only women ≤ 40 years old who underwent single fresh blastocyst transfer and had singleton life births were included in the study. LBW was the primary outcome of this study. Neonatal malformation was the secondary outcome. Multivariable logistic regression was used to evaluate the association between (EMT) ≤7.5 mm and singleton LBW. Results: A total number of 2847 women met the study inclusion criteria. The neonatal birthweight in the EMT ≤7.5 mm group was significantly lower than that in the EMT 7.6~12.0 mm and EMT >12.0 mm group (P<0.001). The rate of LBW in the EMT ≤7.5 mm group was 24.9%, which was significantly higher than the 4.0% in the EMT 7.6~12.0 mm group and the 5.3% in the EMT >12.0 mm group (P<0.001). The total neonatal malformation rate was similar between the groups (1.1%, 0.8% and 1.5%, P=0.21). After multiple regression analysis, EMT ≤7.5 mm was found to be an independent risk factor for LBW (adjusted odds ratio [AOR]: 4.39, 95% CI: 1.85～10.46, P<0.001). Conclusion: EMT ≤7.5 mm on the hCG trigger day is an independent risk factor for LBW in singleton pregnancies from single fresh blastocyst transfer. The neonatal birthweight in the EMT ≤7.5 mm group was significantly lower than that in the EMT 7.6~12.0 mm and EMT >12.0 mm groups. The total neonatal malformation rate was comparable between the groups.